2022
DOI: 10.2147/ijgm.s373015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Conbercept Treatment on Macular Edema and Microvascular Structure in Eyes with Retinal Vein Occlusions

Abstract: Objective To evaluate the efficacy on best corrected visual acuity (BCVA) and microvascular structure changes of conbercept intravitreal injection for the treatment of macular edema (ME) secondary to different types of retinal vein occlusion (RVO) and to explore the baseline OCTA parameters which were related to the change of BCVA and CRT after the intravitreal conbercept injection to RVO. Methods A retrospective observational study was conducted involving 67 eyes from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…RME is the main cause of severe visual impairment in patients with RVO [10] . Currently, the primary treatments for patients with RVO are vitreous injection, laser photocoagulation, and vitrectomy [11][12][13] . Intravitreal injection of anti-vascular endothelial growth factor (VEGF) drugs can significantly improve visual acuity loss caused by RME [14] , and laser photocoagulation is often performed in patients with intraocular neovascularization [15] .…”
Section: Introductionmentioning
confidence: 99%
“…RME is the main cause of severe visual impairment in patients with RVO [10] . Currently, the primary treatments for patients with RVO are vitreous injection, laser photocoagulation, and vitrectomy [11][12][13] . Intravitreal injection of anti-vascular endothelial growth factor (VEGF) drugs can significantly improve visual acuity loss caused by RME [14] , and laser photocoagulation is often performed in patients with intraocular neovascularization [15] .…”
Section: Introductionmentioning
confidence: 99%
“…ME due to RVO (RVO-ME) is sight-threatening and unlikely to improve without treatment [4] , but can be treated by antivascular endothelial growth factor (anti-VEGF) drugs. Recent trials have shown that anti-VEGF therapies (ranibizumab, aflibercept and conbercept) can improve ME in RVO-ME patients [5][6][7] . Ranibizumab was the first and most extensively used anti-VEGF drugs [8] .…”
Section: Introductionmentioning
confidence: 99%